A pilot study of post-exposure prophylaxis for hepatitis C virus in healthcare workers - Corey, Kathleen E (Infect Control Hosp Epidemiol, 2009)
BACKGROUND AND OBJECTIVE: Hepatitis C transmission occurs in 0.2–10% of accidental needle-stick exposures. However, post-exposure prophylaxis is not currently recommended. We sought to determine the safety, tolerability and acceptance of post-exposure prophylaxis with peginterferon in healthcare workers exposed to blood from hepatitis C-infected patients. DESIGN: Open label pilot trial of peginterferon for hepatitis C post-exposure prophylaxis. SETTING: Two academic tertiary-referral centers. METHODS: Healthcare workers exposed to blood from hepatitis C infected patients were informed of the availability of post-exposure prophylaxis. Persons who elected post-exposure prophylaxis were given weekly doses of peginterferon alfa-2b for 4 weeks. PARTCIPANTS: Healthcare workers. RESULTS: Among 2,702 HCWs identified with potential exposures to blood-borne pathogens, 213 (7.9%) were exposed to an anti-HCV-positive source. Of 51 HCWs who enrolled in the study, 44 (86%) elected to undergo post-exposure prophylaxis (Treated Group). Seven subjects elected not to undergo post-exposure prophylaxis (Untreated Group). No cases of hepatitis C virus transmission were observed in either the Treated or Untreated Groups and no cases occurred in the remaining 162 HCWs who did not enroll in this study. No serious adverse events related to PEG-IFN were recorded, but side effects were frequent. CONCLUSION: In this pilot study, there was a lower than expected frequency of hepatitis C transmission after accidental occupational exposure. Although peginterferon was safe, because of the lack of hepatitis C transmission in either the Treated or Untreated Groups, there is little evidence to support routine post-exposure prophylaxis against hepatitis C in healthcare workers.